Adaptive 1-D Polynomial Coding of C621 Base for Image Compression (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The optimal solution to the difficult issues associated with bytes consumption of digital images is to utilize image compression techniques that essentially based on exploiting redundancy(s) efficiently to minimize image size for storage requirements and /or fast transmitted. 1-D polynomial coding is a simple form of the common 2D- polynomial coding that based on modeling spatial image block information using the 1-D nature, which implicitly diminished the extra coefficients of deterministic part and leads to improved compression performance. In this paper, Adaptive 1-D Polynomial Coding for grayscale image compression is proposed with adopting a new compress scheme of six to one data (C621) base for probabilistic part (residual image) effectively, The experimental results tested on six standard gray square images of medical and natural bases, the results showed elegant performance in terms of CR and PSNR compared to the traditional   1-D coding techniques and the well-known standard JPEG, that the compression ratio increase more than three times compared to the traditional 1-D and with higher quality compared to JPEG for the images converged to the same compression performance.